A new chondrichthyan (Sharks and Rays) Fossil Assemblage from the Miocene Cacela Fm. at Albufeira (Algarve, Portugal) with two new species: Palaeoecology and Biogeography - Landau, Bernard M.; Hovestadt, Dirk C.; Silva, Carlos M. Da (Zootaxa, 2025)
A diverse Upper Miocene, Tortonian, assemblage of chondrichthyan fossils from the Cacela Formation, Algarve, southern Portugal, has been studied for the first time. The fossils were collected using bulk and search sampling techniques. Bulk sampling of 100 kg of sediment yielded 319 specimens. Search sampling resulted in 2260 specimens. A total of 32 species were identified, some using open nomenclature. The best represented species in the bulk sample are: Taeniurops cavernosa (Probst, 1877), Carcharhinus acuarius (Probst, 1879), Negaprion eurybathrodon (Blake, 1862), Paragaleus pulchellus (Jonet, 1966) and Rhizoprionodon ficheuri (Joleaud, 1912), making up 20% of the species and 55% of the specimens in the sample. Carcharhinus cf. ambionensis, C. cf. brachyurus, C. cf. brevipinna and C. cf. sorrah are reported for the first time from the Miocene. Kruckowlamna cf. costarricana Laurito Mora, 1999, previously known only from the Mio-Pliocene of the Caribbean, is a new record for the European Miocene. Two new species were identified: Chiloscyllium serralheiroi sp. nov. and Palaeorhincodon fialhoi sp. nov., also representing the first record of these genera for the Miocene. The fauna documented in the study assemblage is interpreted as having inhabited a neritic shallow marine subtropical to, most probably, tropical environment. Several thermophilic taxa represented in the study assemblage—e.g., Taeniurops, Negaprion, Paragaleus, etc.—are currently found at lower subtropical and tropical latitudes in the Atlantic. This Neogene to Holocene southward range contraction is consistent with similar biogeographical trends observed in other marine groups, namely, among benthic molluscs.